A 4-Week Repeated Oral Dose Toxicity Study of Ssanghwa-Tang in Crl:CD Sprague Dawley Rats. (16th May 2019) - Yoo, Sae-Rom; Ha, Hyekyung; Lee, Mee-Young; Shin, Hyeun-kyoo; Han, Su-Cheol; Seo, Chang-Seob
Abstract : Ssanghwa-tang (SHT), a traditional herbal formula, has been widely used to recover fatigue or consumptive disease after an illness. Along with much attention to herbal formula, the concerns about the safety and toxicity have arisen. To establish the safety information, SHT was administrated in Crl:CD Sprague Dawley rats at a daily dose of 0, 1000, 2000, and 5000 mg/kg for 4 weeks. During the test periods, we examined the mortality, clinical observation, body weight change, food consumption, organ weights, hematology, serum biochemistry, and urinalysis parameters. No changes of mortality and necropsy findings occurred in any of the groups during the experimental period. In either sex of rats treated with SHT at 5000 mg/kg/day, changes were observed in food intake, reticulocyte, total bilirubin, some urinalysis parameters, and relative organ weights. The results indicated that SHT did not induce toxic effects at a dose level up to 2000 mg/kg in rats. This dosage was considered no observed adverse effect level (NOAEL) and was appropriate for a 13-week subchronic toxicity study.